Golden child : a novel - Adam, Claire (SJP for Hogarth, 2019)
Rural Trinidad: a brick house on stilts surrounded by bush; a family, quietly surviving, just trying to live a decent life. Clyde, the father, works long, exhausting shifts at the petroleum plant in southern Trinidad; Joy, his wife, looks after the home. Their two sons, thirteen years old, wake early every morning to travel to the capital, Port of Spain, for school. They are twins but nothing alike: Paul has always been considered odd, while Peter is widely believed to be a genius, destined for greatness. When Paul goes walking in the bush one afternoon and doesn't come home, Clyde is forced to go looking for him, this child who has caused him endless trouble already, and who he has never really understood. And as the hours turn to days, and Clyde begins to understand Paul<U+2019>s fate, his world shatters<U+2014>leaving him faced with a decision no parent should ever have to make.Like the Trinidadian landscape itself, GOLDEN CHILD is both beautiful and unsettling; a resoundingly human story of aspiration, betrayal, and love.